Modelling, control and simulation of a mobile robot for obstacle avoidance - Yeoh, Guan Wei (Nanyang Technological University, 2024)
Mobile robots can be found in the daily lives of people, from warehouses to restaurants. The ability for it to avoid obstacles is crucial to its operation. Existing obstacle avoidance algorithms help to control the robot, ensuring that it does not collide with any obstacles. Research has been done continuously in this field to improve these algorithms. In this project, some obstacle avoidance algorithms, namely Artificial Potential Field and Fuzzy Logic Control, were analysed and implemented in MATLAB Simulink. A model of a two-wheeled differential drive mobile robot was used to test the algorithms through simulations. The tests include navigating in narrow spaces, reaching a target behind a wall, and traveling through a maze. The results were analysed, and a comparison was made between the two algorithms. It was found that the Fuzzy logic control performed better in most of the test cases. An attempt was made to integrate both algorithms.